2017
DOI: 10.1158/1078-0432.ccr-16-0869
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Receptor Ectodomain Shedding in Treatment, Resistance, and Monitoring of Cancer

Abstract: Proteases known as sheddases cleave the extracellular domains of their substrates from the cell surface. The A Disintegrin and Metalloproteinases ADAM10 and ADAM17 are among the most prominent sheddases, being widely expressed in many tissues, frequently over-expressed in cancer, and promiscuously cleaving diverse substrates. It is increasingly clear that the proteolytic shedding of transmembrane receptors impacts pathophysiology and drug response. Receptor substrates of sheddases include the cytokine receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 69 publications
4
89
0
Order By: Relevance
“…Previous studies have shown that ADAM17 is responsible for the shedding of numerous receptors for oncogenic growth factors, cytokines and adhesion molecules, including VCAM1 [18]. Meanwhile, aberrant ADAM17 expression is related to aggressive lung cancer and poor prognosis [19]. Recently, it was reported that Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry the incubation was continued for an additional 2 h. The absorbance value (OD) was measured at 450 nm using a microplate reader (Varioskan Flash, Thermo Scientific, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ADAM17 is responsible for the shedding of numerous receptors for oncogenic growth factors, cytokines and adhesion molecules, including VCAM1 [18]. Meanwhile, aberrant ADAM17 expression is related to aggressive lung cancer and poor prognosis [19]. Recently, it was reported that Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry the incubation was continued for an additional 2 h. The absorbance value (OD) was measured at 450 nm using a microplate reader (Varioskan Flash, Thermo Scientific, USA).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are well in line with previous observations. Noteworthy, the ectodomains of these receptors are released upon cleavage by sheddases like ADAM10 and ADAM17, and conditions of shedding as well as the function of the soluble ectodomains are incompletely understood . The shedded receptors can have antagonistic function or act as signal mediators.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activity of HER2/HER3 signaling can be further potentiated through ADAM10/17-dependent shedding and activation ErbB ligands (e.g. heregulins)[103, 106, 107, 130132]. It is also appreciated that HER2 receptor can undergo ectodomain cleavage by ADAM10.…”
Section: Adam10 and Intestinal Tumorigenesismentioning
confidence: 99%